CDDPath: A method for quantifying the loss and recovery of construction and demolition debris in the United States. (1st February 2019) - Townsend, Timothy G.; Ingwersen, Wesley W.; Niblick, Briana; Jain, Pradeep; Wally, Jim
Highlights: CDDPath provides CDD disposition estimates that complement generation estimates. The CDDPath method combines waste characterization estimates with US state and industry data. ∼140 MMT of CDD materials were estimated to go to landfill in 2014. ∼400 MMT of CDD materials were estimated to be recovered for further use in 2014. Abstract: National generation estimates for seven material types in the construction and demolition debris stream are regularly published in the United States. However, the quantities of these materials in different end-of-life management pathways are not published or otherwise made available. Quantification of end-of-life management pathways is useful for identifying approaches to decrease disposal and increase material recovery. An issue for construction and demolition debris is that data needed for a nationwide estimate of management pathways are not tracked in a single system. We propose and outline a method that draws on a combination of data sources, including nationwide generation estimates, state data, industry association data, and recovery facility reports. Capturing the available data and using the proposed method, we can estimate what end-of-life pathways are used for the seven materials in the US Environmental Protection Agency's annual reports of CDD generation (steel, wood products, drywall and plaster, brick and clay tile, asphalt shingles, concrete and asphalt concrete), and five additional materials managed within the CDD waste stream (carpet, plastic, glass, cardboard and organics). Method results indicate that the vast majority of CDD concrete and asphalt pavement, which in 2014 constituted ∼78% of the overall mass of the stream's components, were reclaimed for use, primarily in road projects. A significant opportunity for material recovery still exists for the remaining ∼22% of the stream. In 2014, approximately 64% of these remaining materials in the US was ultimately routed for landfill disposal.